Meaningful use of collected local roads data and information - McNinch, Terance; Silva, Fernando De Melo e; Gadgil, Kedar; Dong, Jianping (Midwest Regional University Transportation Center, 2008)
There are more than 39,000 local agencies managing 2,000,000 miles of roads throughout the United States. The responsibility for such an immense infrastructure network in a time of limited resources demands the application of contemporary pavement management principles. Yet, the vast majority of these agencies could be classified as small or rural, and implementation of management systems and practices is a significant challenge. The study analyzed responses of an extensive survey completed by over 400 local agencies throughout the upper Midwest. The report identifies current pavement management practices, factors that promote management system implementation, and the challenges (organizational, cultural and technical) that impede implementation. Pavement management systems used throughout the U.S. were cataloged along with capabilities and system specifics. Training available in the survey states was identified and cataloged, and training objectives were applied against a Body of Knowledge Framework. Researchers also conducted in-depth review of the models that had been adopted for use in the RoadSoft? GIS Pavement Strategy module. This review reconsidered the original assumptions of the models, made adjustments to conform to those assumptions, and used actual condition data (three counties, 1733 data points) to compare the output of the new models The findings are of value to FHWA, state DOTs, local agencies, universities and technology transfer centers in their efforts to expand pavement management system implementation within cities, counties, towns, and villages.
167 p.
Keywords: Asset management; Rural highways; Urban highways; Midwestern States; Pavement management systems; Local government agencies